Keterkaitan Sifat Sabar dan Optimisme dalam Hadis Nabi: Tinjauan Tekstual dan Kontekstual serta Relevansinya dengan Terapi Self Talk Positif - Rachmat Bin Badani Tempo (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
This research aims to determine the relationship between patience and optimism based on the perspective of the hadith of the Prophet Muhammad. This research is descriptive research using library methods and a ma'ani hadith study approach. The results of this research found several things. First, the Hadith of Abu Hurairah which is the basis of this research is considered valid in terms of sanad and matan. Second, textually, Abu Hurairah's hadith emphasizes the importance of faith, physical strength and enthusiasm in worship and encourages people to be serious in their efforts while asking for Allah's help, and to be patient when facing disaster without saying